2007
DOI: 10.1104/pp.106.092585
|View full text |Cite
|
Sign up to set email alerts
|

The MtMMPL1 Early Nodulin Is a Novel Member of the Matrix Metalloendoproteinase Family with a Role in Medicago truncatula Infection by Sinorhizobium meliloti  

Abstract: We show here that MtMMPL1, a Medicago truncatula nodulin gene previously identified by transcriptomics, represents a novel and specific marker for root and nodule infection by Sinorhizobium meliloti. This was established by determining the spatial pattern of MtMMPL1 expression and evaluating gene activation in the context of various plant and bacterial symbiotic mutant interactions. The MtMMPL1 protein is the first nodulin shown to belong to the large matrix metalloendoproteinase (MMP) family. While plant MMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 74 publications
4
62
0
Order By: Relevance
“…Importantly, in situ hybridizations showed that Mt RR4 and more generally the type-A response regulator gene family are expressed in nodule zone II, consistent with the EFD expression pattern (see Supplemental Figure 9 online). Other nodulin genes expressed in nodule zone II, such as Mt N6 (Mathis et al, 1999), Mt ENOD11 , and Mt MMPL1 (Combier et al, 2007), were not found to be similarly affected in the efd-1 and P35S:EFD:VP16 samples (see Supplemental Table 5 online).…”
Section: Possible Targets Of the Efd Transcription Factor Revealed Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in situ hybridizations showed that Mt RR4 and more generally the type-A response regulator gene family are expressed in nodule zone II, consistent with the EFD expression pattern (see Supplemental Figure 9 online). Other nodulin genes expressed in nodule zone II, such as Mt N6 (Mathis et al, 1999), Mt ENOD11 , and Mt MMPL1 (Combier et al, 2007), were not found to be similarly affected in the efd-1 and P35S:EFD:VP16 samples (see Supplemental Table 5 online).…”
Section: Possible Targets Of the Efd Transcription Factor Revealed Bymentioning
confidence: 99%
“…As a negative control, to detect any possible nonspecific trans-activation effect, we used a Mt MMPL1 promoter:GUS fusion not controlled by EFD (previous array analyses) and showing a very low basal level of expression in these tissues (Combier et al, 2007). Quantitative analyses of GUS activity in N. benthamiana leaf extracts revealed that the Mt RR4 promoter was clearly activated (on average 8.5-fold on three biological repetitions) by either EFD:RFP ( Figures 9A and 9B) or EFD:HA fusions (see Supplemental Figure 11 online).…”
Section: Efd Activates the Expression Of Mt Rr4 A Gene Encoding A Rementioning
confidence: 99%
See 1 more Smart Citation
“…A small number of genes have been previously determined, by Northern blot analysis or real-time PCR, to be differentially expressed between wild-typeand exo mutant-inoculated roots (34)(35)(36)(37). Our data set, which represents roots harvested at 3 dpi, is earlier than the time points at which expression was assayed for most of the genes previously determined to be differentially expressed (34)(35)(36).…”
Section: Further Comparisons With Other Studiesmentioning
confidence: 99%
“…Several matrixins have been isolated from plants, including soybean (Graham et al, 1991;Liu et al, 2001;McGeehan et al, 1992;Pak et al, 1997), Arabidopsis (Maidment et al, 1999;Golldack et al, 2002), cucumber (Delorme et al, 2000), alfalfa (Combier et al, 2007), Pinus taeda (Ratnaparkhe et al, 2009), and Nicotiana tabacum (Schiermeyer, 2009). Matrixins have zinc at their catalytic center and are sensitive to EDTA (McGeehan et al, 1992).…”
mentioning
confidence: 99%